1998
DOI: 10.1093/rheumatology/37.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of cyclosporin a neoral in the treatment of paediatric lupus nephritis with heavy proteinuria

Abstract: Cyclosporin A (CsA) was introduced in recent years for the treatment of lupus nephritis in patients with steroid resistance or in those with severe corticosteroid toxicity. Our previous study on paediatric patients showed that Neoral (a new microemulsion formulation) had better bioavailability than CsA capsules. To evaluate the clinical efficacy of Neoral in children with lupus nephritis compared with conventional therapy, we performed an open randomized study on 40 children, ranging from 9 to 14 yr old, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 0 publications
0
53
2
1
Order By: Relevance
“…Therefore, in this study, it was adopted blood trough concentration of 80-150 ng/mL, as an effective and less toxic from the previous reports. [13][14][15][16][17][18][19] Administration plans for cyclosporine based on the area under the blood concentration-time curve (AUC) for transplantation patients have been extensively investigated and directions for use have been established. In recent years, Nagai et al reported 32) that the AUC was useful for monitoring the clinical and adverse effects of cyclosporine in dermatomyositis-associated progressive interstitial pneumonia patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, in this study, it was adopted blood trough concentration of 80-150 ng/mL, as an effective and less toxic from the previous reports. [13][14][15][16][17][18][19] Administration plans for cyclosporine based on the area under the blood concentration-time curve (AUC) for transplantation patients have been extensively investigated and directions for use have been established. In recent years, Nagai et al reported 32) that the AUC was useful for monitoring the clinical and adverse effects of cyclosporine in dermatomyositis-associated progressive interstitial pneumonia patients.…”
Section: Discussionmentioning
confidence: 99%
“…rine was maintained at 80-150 ng/mL [13][14][15][16][17][18][19] in a steady state was calculated as the ratio of the number of simulated patients to the total number of patients.…”
Section: Model Evaluation and Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…In an open randomized trial, 40 children with class III-V LN received either CSA or a combination of oral cyclophosphamide with corticosteroids for 1 year (26). Both groups showed equivalent efficacy in terms of reduction in proteinuria and autoantibody levels with preservation of renal function.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%